Pengenalan Organ Reproduksi pada Remaja Putri di SMA Isen Mulang Kota Palangka Raya - Wahidah Sukriani; Riny Natalina (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
Talking about reproductive health is still considered sacred and taboo for some people in Indonesia. Reproductive Health is a topic that woman need to know to have the right information about the reproductive process that begins with the reproductive organs. Problems related to reproductive health often stem from a lack of information, understanding, and awareness to achieve a healthy state of reproduction With the right information, it is expected that adolescents have a responsible attitude and behavior regarding the reproductive process. The purpose of this community service is to introduce the reproductive organs in young women in SMA Isen Mulang Palangka Raya. The method used is to form peer counselors in the effort of the introduction of reproductive organs in young women in Isen Mulang High School Palangka Raya. The result of this service activity shows improvement of knowledge about female reproductive organs, reproductive organ function and how to keep reproductive organs, improving peer counseling skills in peer counseling on women's reproductive organs and the formation of students' attitude to maintain healthy reproduction organs.